Challenges in mental health nursing: Working in institutional or community settings? - Farmakas, Antonis; Papastavrou, Evridiki; Siskou, Olga Ch; Karayiannis, George; Theodorou, Mamas (My University, 2014)
The work environment is an important factor for the delivery of safe and quality care and the retention of healthcare professionals. Mental health nurses working in institutions perceive professional environment more negatively when compared with those working in the community. Perceptions of work motivation, leadership and autonomy are lower when nurses work in psychiatric institutions. More research to investigate the reasons why these weaknesses appear in the working environment is needed. Professional environments likely affect patient safety, quality of care provided, and nurses' satisfaction and retention. The aim of this study was to explore mental health nurses' perceptions of their professional practice environment and examine differences in perceptions between nurses working at institutions and those practising in community care. The methodology used was descriptive and comparative. The sample consisted of 248 mental health nurses working within the public sector (76% response rate) drawn from a psychiatric hospital (n = 163) and community settings (n = 85). We administered the Revised Professional Practice Environment (RPPE) questionnaire. Comparisons of the two groups were made using eight subscales of the RPPE. The results indicated that mental health nurses' ratings of their practice environment were slightly positive (M = 2.69; range = 1-4). Nurses working in a psychiatric hospital perceived the professional practice environment more negatively (M = 2.66) than their colleagues in community care (M = 2.73). A t-test comparison revealed statistically significant differences between the two groups within subcategories of work motivation (P = 0.04) and leadership and autonomy (P = 0.03). Nurses working in the community gave higher ratings in comparison with their colleagues working in institutional settings. In conclusions, an in-depth analysis of differences in practice environments is required to define causes of these differences and how they might influence nurses' abilities to provide quality care.
Keywords: Professional practice environment scale; Mental health nursing; Professional practice environment